(untitled) (Open Herald: Periodical of Methodical Research, 2024)
Content analysis of publications in sociology of medicine had showed some actual social problems of medicine, which became interested for Russian researches in last 10-15 years. These difficulties don’t limited all social problems of medicine and therefore it seems appropriate to new researches in the given direction